2021
DOI: 10.21037/apm-21-858
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonitis, appendicitis, and biliary obstruction during toripalimab treatment in a patient with extensive-stage small-cell lung cancer: a case report

Abstract: In recent years, immune checkpoint inhibitors (ICIs) have become a standard treatment for patients with advanced lung cancers. With the widespread use of immunotherapy in clinical practice, immunerelated adverse events (irAEs) have become increasingly common. This case report details a 72-year-old man with small-cell lung cancer (SCLC) who developed pneumonitis, appendicitis, and biliary obstruction during treatment with toripalimab. The patient was initially diagnosed with limited-stage SCLC in January 2019 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Wen et al documented the initial occurrence of simultaneous pneumonitis and autoimmune DM [33]. Qu et al observed a series of adverse events, including appendicitis, biliary obstruction, and pneumonitis, manifesting sequentially in a single patient [31]. Cases of rare events not only present diagnostic challenges but also complicate treatment, as evidenced by a report by Nakai et al on colitis combining CMV infection [41].…”
Section: Discussionmentioning
confidence: 99%
“…Wen et al documented the initial occurrence of simultaneous pneumonitis and autoimmune DM [33]. Qu et al observed a series of adverse events, including appendicitis, biliary obstruction, and pneumonitis, manifesting sequentially in a single patient [31]. Cases of rare events not only present diagnostic challenges but also complicate treatment, as evidenced by a report by Nakai et al on colitis combining CMV infection [41].…”
Section: Discussionmentioning
confidence: 99%
“…CIP is one of the major causes of ICI-associated mortality (16). Symptoms of CIP include dry cough, shortness of breath with exertion, reduced oxygen saturation and bilateral ground-glass opacities or patchy nodular infiltrations in the lung on CT imaging (27,28). The incidence of pneumonia secondary to ICIs is <5%, with fatal CIP being reported in 0.2-0.5% patients (16,29).…”
Section: Discussionmentioning
confidence: 99%
“…At present, the patient has been treated with 32 cycles of Toripalimab, during treatment tumor markers have decreased significantly, the primary and metastatic lesions have shrunk or disappeared. (Qu, Y., et al, 2021).…”
mentioning
confidence: 99%